The Role of WhatsApp Social Media in the Spreading of Community-Based Bil Tadwin Preaching: A Case Study of Ustadz Hanan Attaki's Preaching Channel - Kahfi, Al (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
This study examines the role of WhatsApp as a community-based da'wah bil tadwin media, focusing on Ustadz Hanan Attaki's da'wah channel, which uses a one-way communication format. This study aims to analyze the effectiveness of WhatsApp in spreading da'wah to a wide and diverse audience, while exploring how this approach allows full control over da'wah content. Using a qualitative method with a case study approach, data were obtained through observation of message content, interviews with community members, and analysis of literature related to digital da'wah. The study results indicate that WhatsApp's one-way format effectively maintains the consistency of da'wah messages, reduces the risk of information distortion, and maximizes control of narrative quality. Messages delivered through the bil tadwin format, such as inspirational quotes, study materials, and calls for goodness, were well received without direct interaction. This shows that the one-way approach on WhatsApp provides advantages in controlling the quality of da'wah messages, maintaining narrative consistency, and reducing the risk of information distortion. Messages delivered through the bil tadwin format, such as inspirational quotes, study materials, and calls for goodness, were well received by the audience, even without direct interaction. In addition, the private nature of WhatsApp helps create an exclusive and focused environment for the da'wah community, where the audience feels more connected to the religious message being conveyed.